Essays on Music - Adorno, Theodor W. 1903-1969; Leppert, Richard D.; Gillespie, Susan H. (Berkeley, CA University of California Press, 2002)
Theodor W. Adorno (1903-1969), one of the principal figures associated with the Frankfurt School, wrote extensively on culture, modernity, aesthetics, literature, and--more than any other subject--music. To this day, Adorno remains the single most influential contributor to the development of qualitative musical sociology which, together with his nuanced intertextual readings of musical works, gives him broad claim as a continuing force in the study of music. This long-awaited collection of twenty-seven essays represents the full range of Adorno's music writing. Nearly half of the essays appear in English for the first time; all of the essays are fully annotated; and the previously translated essays have been corrected and missing text restored, making this volume the definitive resource on Adorno's musical thought.
Keywords: 20th Century (1901-2000); Music philosophy and esthetics; Germany